Regulatory Compliance and Ethical Governance in Umrah Services: Assessing Pilgrim Protection in Indonesia - Mahmudi Affan Rangkuti; Hendri Tanjung; Indupurnahayu; Trisiladi Supriyanto (CV. FOUNDAE, 2026)
Background: The governance of Umrah services in Indonesia formally emphasizes sharia compliance and regulatory control as mechanisms for protecting pilgrims. However, recurring problems in service delivery suggest a gap between procedural compliance and the substantive protection expected within religious service administration. Aims: This study aims to examine how regulatory compliance and ethical governance influence the protection of Umrah pilgrims in Indonesia by assessing whether existing governance mechanisms provide substantive protection or remain limited to procedural compliance. Method: The study adopts a normative–empirical approach by examining statutory regulations, policy instruments, and supervisory mechanisms governing Umrah services. These regulatory frameworks are analyzed alongside institutional documents and implementation records to assess how compliance mechanisms operate in practice. Results: The findings indicate that pilgrim protection is predominantly pursued through procedural mechanisms such as licensing systems, administrative reporting, and digital monitoring platforms. Nevertheless, these instruments do not consistently produce strong and enforceable protection across the Umrah service chain. In many cases, sharia compliance functions primarily as formal adherence to regulatory requirements rather than as an ethical commitment to safeguarding pilgrims’ rights and service reliability. Conclusion: The study concludes that effective pilgrim protection requires a shift from procedural compliance toward ethical governance and substantive regulatory accountability. Strengthening institutional compliance mechanisms and integrating ethical principles into regulatory supervision are essential for ensuring that sharia compliance functions as a meaningful instrument of protection rather than merely an administrative standard.